Projecting The Employability Of Gen Z: A Mixed-Method Analysis Of Soft Skill Competencies Acquired Through College Education - Lakshmi H, Seetha; S. Jayakani, S. Jayakani (Journal of Neonatal Surgery, 2025)
As Generation Z enters the workforce, there is a growing concern about their readiness to fit in project teams. This paper aims to investigate the soft skill competencies acquired by Gen Z through college education and its impact on their employability. A mixed-method approach is used, which includes a literature review and an empirical study involving a survey of 302 college students about to enter the labor market. The study reveals that while Gen Zers have some of the essential soft skills, there is a need to develop their self-awareness of their strengths and weaknesses. The study also identifies a significant correlation between the most highlighted Generation Z traits and essential project management soft skills, indicating that Gen Zers possess the potential to be valuable assets in the project management field. However, the study finds that other essential soft skills required for employability are not grounded in personality traits. The paper concludes by offering insights for educators and organizations on how to better prepare and support Gen Zers in developing the soft skills required for employability.